Public and private sector wages: co-movement and causality - Ana Lamo; Javier J. Pérez; Ludger Schuknecht (European Central Bank (ECB), 2008)
This paper looks at public and private sector wages interactions since the 1960s in the euro area, euro area countries and a number of other OECD countries. The paper reports, first, a strong positive annual contemporaneous correlation of public and private sector wages over the business cycle; this finding is robust across methods and measures of wages and quite general across countries. Second, we show evidence of long-run relationships between public and private sector wages in all countries. Finally, causality analysis suggests that feedback effects between private and public wages occur in a direct manner and, importantly also via prices. While influences from the private sector appear on the whole to be stronger, there are direct and indirect feedback effects from public wage setting in a number of countries as well. We show how country-specific institutional features of labour and product markets contain helpful information to explain the heterogeneity across countries of our results on public/private wage leadership.
Keywords: C32; J30; J51; J52; E62; E63; H50; 330; (partly) government wages; causality; co-movement; private sector wages; Lohnniveau; Vergütungssystem im öffentlichen Dienst; Lohn; Öffentlicher Dienst; Privatwirtschaft; EU-Staaten